2021
DOI: 10.1155/2021/9914048
|View full text |Cite|
|
Sign up to set email alerts
|

Design of Teaching Video Resource Management System in Colleges and Universities based on Microtechnology

Abstract: The video management system in colleges and universities has become one of the most important platforms for video communication. In order to improve the storage and sharing of teaching video resource system in colleges and universities, this paper designs a teaching video resource management system based on micro grid technology. Through the construction of microtechnology + NAS network storage, the video network storage is realized, and the network sharing efficiency is improved. In addition, ASP.NET is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In the construction phase of the tree, the data are recursively divided into subsets, and all records in each subset belong to the same class or each subset is small enough to build a tree number. e bones of a tree are characteristic, and the edges of the tree are the result of characteristics [14]. e flowchart is shown in Figure 2.…”
Section: Decision Tree Classificationmentioning
confidence: 99%
“…In the construction phase of the tree, the data are recursively divided into subsets, and all records in each subset belong to the same class or each subset is small enough to build a tree number. e bones of a tree are characteristic, and the edges of the tree are the result of characteristics [14]. e flowchart is shown in Figure 2.…”
Section: Decision Tree Classificationmentioning
confidence: 99%
“…One is that users graft and train the encryption storage module of teaching resources by themselves. For the school that lacks practical and technical talents in network and intelligent computing technology, the cost of designing the encryption storage system of teaching resources alone is too high, and it is technically impossible to achieve to a certain extent [13]; the second is to use it by renting a third-party encrypted storage model. Although this method can solve its own technical shortcomings, the maintenance cost is still relatively high, and the encrypted storage process is controlled by the third-party organization in the whole process, which has a certain risk; the third is to use cloud platform services for teaching resource storage [14].…”
Section: A Design Of Cloud Platform Storage Encryption Methods Based ...mentioning
confidence: 99%
“…He created a microgrid-based teaching video resource management system to improve the storage and sharing of teaching video resource systems in colleges and universities. He realized video network storage and improved network sharing efficiency by constructing micro-technology network storage [ 3 ]. Tucker et al found that one of the main difficulties in achieving effective online teaching was the difficulty of accessing the vast teaching resources of teachers.…”
Section: Related Workmentioning
confidence: 99%